INFORMATION SYSTEMS PLANNING AND CONTROL IN PT.TERANG KITA MACHINERY PARTS. - Saepul Lukman; Irwan Bastian, SKom, MM Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1998)
Material Information System and Spare Parts are running currently in the PT.TerangKita not support effective management decisions in the planning inventory cadangatribe, so the decision becomes inaccurate. This is evident from the fact frequentpurchases of goods that ultimately unused, but on the other hand often also stock outoccurred. Formally planning is based on the number of spare parts usage in the periodin which valid and need an instant, without regard to technical factors, economic, andwithout anticipating the future needs systematically. By analyzing the current systemcan be concluded that the PT.Terang Kita really need a sisttem information that cansupport the planning and controlling inventory of spare parts especially the engine tohelp smooth production and operation.